A small-scale solar organic Rankine cycle combined heat and power system with integrated thermal-energy storage - Freeman,J; Guarracino,I; Kalogirou,SA; Markides,CN (Elsevier, 2017)
In this paper, we examine integrated thermal energy storage (TES) solutions for a domestic-scale solar combined heat and power (S-CHP) system based on an organic Rankine cycle (ORC) engine and low-cost non-concentrating solar-thermal collectors. TES is a critical element of solar-thermal systems. It can allow, depending on how it is implemented, improved matching to the end-user demands, improved load factors, higher average efficiencies and overall performance, as well as reduced component and system sizes and costs, especially in climates with high solar-irradiance variabilities. The operating temperature range of the TES solution must be compatible with the solar-collector array and with the ORC engine operation in order to maximise the overall performance of the system. Various combinations of phase change materials (PCMs) and solar collectors are compared and the S-CHP system's electrical performance is simulated for selected months in the contrasting climates of Cyprus and the UK. The key performance indicator of the ORC engine (net-work output) and the required TES volume are compared and discussed. The PCM-TES solutions that enable the best summer performance from an ORC engine sized for a nominal ~1-kWe output in combination with a 15-m2 solar collector array result in diurnal volume requirements as low as ~100 L in Cyprus and 400 - 500 L in the UK. However, the required TES volume is strongly in influenced by the choice of operational strategy for the system in order to match the domestic load profiles. In a full-storage strategy in which electrical energy generation from the ORC engine is offset to match the week-day evening peak in demand, it is found that a ~20% higher total daily electrical output per unit storage volume can be achieved with a PCM compared to liquid water as a sensible storage medium. The isothermal operation of the PCM during phase-change allows for a smaller diurnal storage temperature swing and a higher energy conversion efficiency